Development of amino-functionalized membranes for removal of microorganism. (August 2018) - Peña-Gómez, Nataly; Ruiz-Rico, María; Fernández-Segovia, Isabel; Barat, José M.
Abstract: Treatments to ensure water supply of an acceptable hygienic-sanitary quality is of vast importance. Among unconventional treatments, membrane technologies have recently stood out. Immobilization of antimicrobial compounds onto membranes can prevent fouling and lead to self-cleaning matrices. In this study, cellulose membranes functionalized with amines were developed to assess their capability to remove microbial contamination. Water samples with several levels of Escherichia coli inoculum were filtered through membranes, and different trials were run to check the system's effectiveness. The amino-functionalized membranes were able to filter water samples in a few seconds, and partially or completely remove the inoculated microorganism depending on the inoculum level. The amine-functionalized membranes displayed significant retention capacity in samples with high bacterial concentrations and were able to decontaminate water with low microbial load. Membranes can be reused with no apparent loss of efficiency. Hence, this study demonstrates the high potential of amine-functionalized membranes in drinking water treatments. Industrial relevance: Filtration represents an important non-thermal process used for clarification, concentration and microbial stabilization of liquid fluids. However, membrane fouling and related cleaning requirements are critical factors determining the extensive application of this technology. This work represents an important starting point to the development of new antimicrobial surfaces due to the demonstrated advantages associated to the covalent immobilization for the development of novel filtration treatment methodologies. Highlights: Design of novel water treatments is an urgent need for public health. Antimicrobial cellulose membranes functionalized with a primary amine were developed. The antimicrobial membranes partly or completely removed Escherichia coli from water.